2015
DOI: 10.1016/j.jlumin.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Blue emission of Eu2+-doped translucent alumina

Abstract: a b s t r a c tInorganic scintillators are very important in medical and industrial measuring systems in the detection and measurement of ionizing radiation. In addition to Ce 3 þ , a widely used dopant ion in oxide scintillators, divalent Europium (Eu 2 þ ) has shown promise as a high-luminescence, fast-response luminescence center useful in the detection of ionizing radiation. In this research, aluminum oxide (Al 2 O 3 ) was studied as a host material for the divalent europium ion. Polycrystalline samples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
(52 reference statements)
1
18
0
4
Order By: Relevance
“…The charge compensation is expected to occur through the formation of oxygen vacancies, which are common in a reducing atmosphere [14,28].In addition, it has been widely reported that this band is related with the 5݀ → 4݂ allowed transition of Eu 2+ ions. The reduction of europium in matrixes formed by trivalent cations and even the presence of a similar band due to Eu 2+ in the Y 2 Si 2 O 7 lattice is found in literature [14,28,33].…”
Section: Figure 2 About Heresupporting
confidence: 75%
“…The charge compensation is expected to occur through the formation of oxygen vacancies, which are common in a reducing atmosphere [14,28].In addition, it has been widely reported that this band is related with the 5݀ → 4݂ allowed transition of Eu 2+ ions. The reduction of europium in matrixes formed by trivalent cations and even the presence of a similar band due to Eu 2+ in the Y 2 Si 2 O 7 lattice is found in literature [14,28,33].…”
Section: Figure 2 About Heresupporting
confidence: 75%
“…Recently, a novel casting system using a water‐soluble, alternating block co‐polymer of isobutylene and maleic anhydride (see Figure ) (trade name: ISOBAM [#104, Kuraray America, Elastomer BU]) has gained interest. It is particularly advantageous because it uses one organic component that purportedly acts as both a binder and a dispersant, while producing dense green bodies with homogenous microstructures at high solids loading (up to 55 vol%), low added organic content (~0.1%‐1%), and low shrinkage and cracking …”
Section: Introductionmentioning
confidence: 99%
“…The catalytic, optical, and structural properties of alumina can be enhanced by doping small amounts of one of the transitional elements including Mn, Zn, Fe, and Cu. Among these transition metals, iron dopant in aluminum oxide improved its catalytic and magnetic properties owing to the increase in surface‐to‐volume ratio . When Fe 3+ ions lie at the alumina surface the absorptivity increases in relation to the volumetric state because of the addition of iron dopant.…”
Section: Introductionmentioning
confidence: 99%